Kondisi Para Pekerja Industri Alas Kaki di Indonesia Pasca Pemutusan Hubungan Kerja (PHK) di Masa Pandemi Global COVID-19 - Genta Mahardhika Rozalinna; Regina Cita Berdida (Brawijaya Journal of Social Science, 2022)
ABSTRACTThe global COVID-19 pandemic has an impact not only on the health sector but also on the industrial sector, especially the footwear industry in various countries such as France, Germany, England, Japan, and also Indonesia. This article discusses specifically the social problems that occur among footwear industry workers in Indonesia after termination of employment (PHK) during the global COVID-19 pandemic. Prior to the pandemic, the footwear industry in Indonesia was running well, and Indonesia was even the fourth country in the world to produce the most footwear in 2018. The production of these footwear was 1.4 billion pairs of footwear which is equivalent to 4.6 percent of the total footwear production worldwide, apart from China, India and Vietnam. The research method used in the writing is descriptive qualitative, which is carried out with data collection methods through in-depth interviews, observations, and journal articles that also discuss problems in the footwear industry. The informants interviewed were a married couple who experienced the termination of employment during the pandemic. The results of this study include: (1) laying off workers, which is one of the options that emerged during the pandemic to close the termination of employment status; (2) when workers were laid off for several months, they did not receive wages, which then led to termination of employment on the grounds that the company is no longer able to carry out production and is declared bankrupt; (3) Workers who have had their employment terminated include both permanent and casual daily workers; (4) casual daily workers who do not receive severance pay; and (5) permanent daily workers who are rehired as casual daily workers.